2022
DOI: 10.3390/bios12070475
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Fetal ECG Monitoring System from Abdominal Electrocardiography Recording

Abstract: Fetal electrocardiography (ECG) monitoring during pregnancy can provide crucial information for assessing the fetus’s health status and making timely decisions. This paper proposes a portable ECG monitoring system to record the abdominal ECG (AECG) of the pregnant woman, comprising both maternal ECG (MECG) and fetal ECG (FECG), which could be applied to fetal heart rate (FHR) monitoring at the home setting. The ECG monitoring system is based on data acquisition circuits, data transmission module, and signal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Nine studies described the application of wearable sensors to collect information about foetal parameters [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. These studies are described in Table 1 , together with a summary of their design and population, wearable device used, and main findings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies described the application of wearable sensors to collect information about foetal parameters [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. These studies are described in Table 1 , together with a summary of their design and population, wearable device used, and main findings.…”
Section: Resultsmentioning
confidence: 99%
“…Their experimental results suggested that the device—which was also integrated with an app for Android smartphones—might be a feasible, non-invasive, monitoring system of foetal ECGs in real time [ 19 ]. Zhang and colleagues proposed a similar monitoring system with three electrodes, which was able to obtain foetal heart rate from the recorded abdominal ECG of pregnant women [ 20 ]. Their validation study was conducted on three pregnant women, showing good signal quality and high accuracy in three different postures (supine, seated, and standing) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These wearable technologies are widely adopted and mainly based on ECG processing techniques. Several devices have been developed for ECG analysis such as Zhang et al [5] used a wearable device for fetal ECG monitoring, Wu et al [6] introduced IoT based ECG monitoring system and integrated on a T-shirt, and Beach et al [7] developed wristworn ECG monitoring system based on IoT systems. Thus, ECG analysis plays an important role.…”
Section: Introductionmentioning
confidence: 99%